The Influence of School Heads’ Transformational Leadership on Schools’ Performance: The Case of City Schools Division of San Fernando, La Union - Dacpano, Edgardo B. (Future Science / FSH-PH Publications, 2022)
The main purpose of the study was to investigate the relationship of school heads’ transformational leadership and school performance among public elementary school in the City Schools Division of San Fernando, La Union. Descriptive-correlational design was used which consists of 27 elementary schools with twenty-seven (27) school heads and four hundred forty-three (443) teachers who were in active service for the School Year 2021-2022 were the respondents of the study. Descriptive statistics, Kruskal-Wallis H test, Wilcoxon signed rank test, Rank-biserial and Spearman’s rank, Pearson product-moment correlation were the tools used in the study and all analyses were tested at 0.05 level of significance using IBM SPSS. The professional characteristics of the school heads showed that majority of them are occupying a plantilla item of Principal 1 and 2 and are still taking their doctorate degree. Also, most of them served for 10 years and above as school heads and they are managing non-central and medium-sized schools. The practice of transformational leadership among the school heads is generally high and the ratings of the school heads across all the dimensions of transformational leadership are consistent. Majority of the school head in the Division of La Union have Maturing or level 2 SBM practice. The schools have introduced and sustained continuous improvement process that integrates wider community participation and improve significantly the students’ performance and learning outcomes. The test of hypothesis showed that there were no significant differences between school heads and teachers’ ratings of the former’s transformational leadership except for the domains “enabling others to act” and “encouraging the heart”. The school type had a significant relationship with the domain “enabling the heart”. Specifically, those who are managing non-central school had significantly lower scores in encouraging the heart compared to those who are managing the central schools. Other profile variables are not significantly related to transformational leadership. Finally, there was a significant positive correlation between the overall transformational leadership and the schools’ performance. The more school heads practice transformational leadership particularly “Inspiring a shared vision” and “Encouraging the heart”, the higher is the schools’ performance. In conclusion, the elementary schools in the Division of La Union City are compliant to DepEd Order No. 83, s. 2012. However, much is desired to elevate its compliance to advanced stage. Significantly, the high practice of transformational leadership and this is translated in the school improvement and performance marked by the introduction and sustained process of stakeholders’ participation and significant students’ learning outcomes. Remarkably, higher practice of transformational leadership among school heads yields higher school performance particularly along Inspiring a shared vision and Encouraging the heart. Thus, transformational leadership is an effective leadership approach in managing DepEd schools as it ushers significant changes in the development of schools and its stakeholders.